CONSUMER PREFERENCES FOR RICE IN MALANG, EAST JAVA, INDONESIA - Anisa Aprilia; Fitrotul Laili; Sujarwo Sujarwo (Agricultural Socio-Economics Journal, 2016)
This research aims to investigate characteristic of rice consumers in Malang and determine which combination of rice attributes that included into consumer preferences. The research method was descriptive analysis and conjoint analysis. The results show that the consumer preferences for rice in Malang are affected by taste, colour, rice grain, packaging size and label. Rice taste that desired by consumers in Malang is a tasty rice. In addition, consumers prefer small packaging, pure white colour and labelled rice product, which contains information related to the rice and brand product.